The Effect of the I-SETS (Islamic- Science, Environment, Technology, Society) Approach on Science Learning Outcomes of Elementary / MI Students - Nailah Rizkiyah Lubis; Salminawati (South Sulawesi Education Development (SSED), 2024)
This study aims to determine whether there is an effect of the I-SETS (Islamic, Sciene, Environment, Technology and Society) approach on student science learning outcomes. This study uses quantitative methods with Quasy Experimental Design type Control group pretest-postest, with the presence of another group called the comparison group or control group, it can be seen from those given treatment compared to those who do not get treatment. The data analysis technique used is descriptive analysis to calculate the mean, median, mode, standard deviation, and variance. Prerequisite analysis with normality test, homogeneity test, and to test the hypothesis in this study used independent t-test. Based on research using the t-test, the Sig. (2-tailed) value is 0.016 <0.05, so Ho is rejected and Ha is accepted, which means that there is an effect of the I-SETS (Islamic- Science, Environment, Technology, Society) approach on student science learning outcomes. For future researchers, in addition to learning outcomes, the I-SETS approach can also be applied to 21st century learning based on 4C skills, namely Critical thinking, Creativity thinking, Collaboration, and Communication.